Rukun Islam Tataran Syariat dan Tarekat dalam Kitab Sirrul Asrar karya Abdul Qadir Al-Jailani - Shofwan, Arif Muzayin (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2022)
Many people understand that the implementation of the pillars of Islam is only sufficient at the level of the birth of the Shari'a. In fact, the implementation of the pillars of Islam does not just stop at the level of the Shari'a. However, the implementation of the pillars of Islam in the world of Sufism should reach the top level, namely tarekat, essence, and makrifat. One of the books that discuss the implementation of the pillars of Islam at the level of Shari'a and nature is the Book of Sirrul Asrar by Shaykh Abdul Qadir Al-Jailani. This qualitative descriptive paper with library studies discusses the implementation of the pillars of Islam in the Shari'a and tarekat levels from the formulation of Sheikh Abdul Qadir Al-Jailai. The data analysis in this paper uses content analysis by sorting out the data according to the research objectives. The findings of this study are as follows. First, the common shari'a creed is embedded in outward speech, while the tarekat creed is embedded in essential knowledge. Second, the shari'a prayer appears on the outside starting with Takbir and ending with greetings at a particular time while the tarekat prayer is performed in mind all the time. Third, sharia fasting is carried out at certain times while tarekat fasting is carried out all the time. Fourth, shari'a zakat is interpreted externally with alms while tarekat zakat is interpreted inwardly with purification of the heart from all lust. Fifth, the sharia pilgrimage is implemented outwardly along with the conditions and pillars to Mecca, while the tarekat pilgrimage is implemented inwardly into self-fulfillment.Keywords :